PENGARUH DISIPLIN KERJA, KEPUASAN KERJA, DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA LPD DESA ADAT MENGWI BADUNG - I Gusti Ayu Sukma Dwi Gayatri; Ketut Setia Sapta; Anak Agung Dwi Widyani (VALUES, 2023)
Facing the current era of increasingly stringent business competition, the performance of employees is required to continue to increase, so that business entities continue to exist, they must have the courage to face them, namely to face change and win the competition. There are three factors that affect employee performance, namely work discipline, job satisfaction, and employee commitment. This study aims to determine the effect of work discipline, job satisfaction, and employee commitment on employee performance at the LPD in Mengwi Traditional Village. The method of determining the sample used is saturated sampling or census method with a total of 37 employees as respondents. The population in this study were employees of the Mengwi Traditional Village LPD. Data collection techniques using documentation, observation, interviews, and questionnaires. The data analysis technique used is quantitative analysis. The results of this study indicate that work discipline, job satisfaction, and employee commitment have a positive and significant effect on employee performance. This means that if work discipline, job satisfaction, and employee commitment increase, employee performance will also increase.